Putinomics : power and money in resurgent Russia - Miller, Chris (Research fellow) (The University of North Carolina Press, 2018)
When Vladimir Putin first took power in 1999, he was a little-known figure ruling a country that was reeling from a decade and a half of crisis. In the years since, he has reestablished Russia as a great power. How did he do it? What principles have guided Putin's economic policies? What patterns can be discerned? In this new analysis of Putin's Russia, Chris Miller examines its economic policy and the tools Russia's elite have used to achieve its goals. Miller argues that despite Russia's corruption, cronyism, and overdependence on oil as an economic driver, Putin's economic strategy has been surprisingly successful.